Regulation of salt tolerance in the roots of Zea mays by L-histidine through transcriptome analysis - Ji, Hongfei; Yang, Guoping; Zhang, Xiu; Zhong, Qiumei; Qi, Yuxi; Wu, Kaihua; Shen, Tingting (Frontiers in Plant Science, 2022)
Salinized land is the main reason for crop yield reduction. Histidine ameliorates the adverse effects of salt stress on maize root growth. Here, However, the underlying regulatory mechanism is unknown. In this experiment, the dose of 0.1 μM histidine to maize roots was exposed to 100 mM NaCl. Exogenous histidine significantly decrease the accumulation of superoxide anion radicals, hydrogen peroxide, and malondialdehyde as well as the content of nitrate nitrogen and ammonium nitrogen was reduced. Histidine treatment significantly increased the activity of superoxide dismutase, peroxidase, catalase, nitrate reductase, glutamine synthetase, and glutamate synthase. Transcriptome analysis revealed that the differentially expressed genes (DEGs) of 454 (65 were up-regulated and 389 were down-regulated) and 348 (293 were up-regulated and 55 were down-regulated) were identified by histidine treatment for 12 h and 24 h respectively under salt stress. Analysis of DEGs related pathways showed that a small number of down-regulated genes were enriched in phytohormone signaling and phenylpropanoid biosynthesis when treated with histidine for 12 h, and DEGs were significantly enriched in phytohormone signaling, glycolysis, and nitrogen metabolism when treated until 24 h. Under salt stress, DEGs and enrichment pathways increased with the increase of histidine treatment time. By tracking the changes of specific gene expression and enzyme activity, We found that histidine could improved the salt tolerance of maize roots through plant hormone signal transduction, glycolysis and nitrogen metabolism